PORTRAYAL OF A PRIYAYI'S WIFE IN PRAMOEDYA ANANTA TOER'S GADIS PANTAI - Eva Silvania, - (2008)
Qualitative descriptive method was used in order to reconstruct the portrayal of a Priyayi's wife in the novel. To collect the data, the novel was read carefully in order to find relevant textual evidences to answer the proposed research questions. Afterward, the data was analyzed by applying Marxist Feminism to analyze factors causing the change of Gadis Pantai characteristics. The findings indicate that characteristics of Gadis Pantai before she gets married are poor, irreligious, out-spoken, and carefree. Meanwhile, Gadis Pantai characteristics after she gets married and becomes a Priyayi's wife have changed. She lacks voice, subordinated, and being exploited. Besides, she has also a positive characteristic that is skillful. Regarding to Marxist feminism, the change of Gadis Pantai's characteristics are caused by different background of Gadis Pantai and Bendoro, her husband, in social, economic, educational, cultural, and religious factors. Gadis Pantai who represents the proletariat class is oppressed by Bendoro who represents the bourgeoisie class. Therefore, it indicates that woman's oppression is not the product of man's actions deliberately. It is the product of politic, social, and economic structures in a society, in which woman inhabits.